The use of rIX-FP in patients with haemophilia B: a nurse's perspective - Garner Kara; Guelcher Christine; Pollard Debra (The Journal of Haemophilia Practice, 2021)
The management of patients with haemophilia is complex and requires lifelong care to be delivered by a specialist multidisciplinary team. Haemophilia B results from a deficiency or absence in coagulation factor IX (FIX), leading to easy bruising, and musculoskeletal and internal bleeding. For patients with severe or moderate haemophilia B, prophylaxis with standard half-life (SHL) coagulation FIX products requires frequent intravenous administration, which may negatively impact treatment adherence and increase burden of care. A recombinant fusion protein linking recombinant FIX (rFIX) with recombinant human albumin, rIX-FP, has an extended half-life compared with SHL rFIX, and has demonstrated a favourable safety and efficacy profile for the prevention and treatment of bleeding episodes in phase III and real-world studies of patients with severe haemophilia B. rIX-FP enables treatment to be tailored to the needs of individual patients, with dosing flexibility allowing selected patients to be treated with prophylaxis dosing intervals of 7, 10, 14 or 21 days. Patients switching to rIX-FP can reduce their annualised bleeding rate and some have successfully reduced their prophylactic dosing frequency while maintaining low bleeding rates and consistent factor consumption. This may ultimately minimise the occurrence of haemophilic arthropathy and improve patient quality of life. Educating patients and caregivers on the sustained use of rIX-FP prophylaxis is essential. The lifelong support and guidance provided by healthcare professionals at haemophilia treatment centres (HTCs) are critical for providing an optimal treatment approach that can increase adherence to treatment. This article reviews the pharmacokinetics, efficacy, and safety of rIX-FP demonstrated in clinical trials and clinical practice, and discusses haemophilia nurses’ clinical experiences with rIX-FP in patients in their HTCs.